Chill-haze – Identification and Determination of Haze-active Constituents by HPLC and Mass Spectrometry: Part I: The role of polyphenols and the astonishing impact of hop components on chill haze formation - Loch-Ahring, Stefan; Decker, Fabienne; Robbert, Sascha; Andersson, Jan (BrewingScience, 2008)
The formation of haze is a serious problem of bright beers because it limits the storage life of the bottled or barrelled product. The problem is particularly evident in the bottle. Haze (chill haze) is said to be caused by different substances and mechanisms. The most commonly held opinion makes a protein polyphenol interaction responsible for its formation. Therefore efforts of the brewing industry are targeted towards a minimization of one or both of these components by filtration through PVPP (polyvinylpolypyrrolidone) and diatomite (Celite). The objective of this study was to trace the influence of polyphenols as well as other phenolic substances on the colloidal stability of beer and to lay the foundation for tracing them throughout the brewing process. In regard to chill haze performance and brewing stabilisation, the repeated reference to polyphenols led us to examine the polyphenol content of isolated chill haze in detail. Based on an existing method normally used to determine the polyphenol composition of beer and wort, a modified approach was developed to examine polyphenols in chill haze. To examine the possible influence of polyphenols on chemo-physical endurance, beer samples taken throughout the brewing process, isolated chill haze and permanent beer turbidity were determined by HPLC-DAD-QTOF-MS, UPLC-DAD-QTOF-MS and nano ESI chip-QTOF-MS. This is the first part of our work and only discusses the polyphenol analysis in wort, beer and isolated haze performed by HPLC-DAD-QTOF-MS and nano ESI chip-QTOF-MS. Haze properties were not studied using kinetics but analytical methods with the aim to identify single components. The influence of some polyphenols on the formation of haze clouding was observed. The strong influence of hop substances on the colloidal stability could be demonstrated.